(untitled) (Global Journal of Human-Social Science, 2023)
From drawing to symbols is a syntactic transcultural reading of the arts as tools of communication and transmission Questionning symbols concerning grieving in relationship to individual message may lead to the understanding of the collective behaviour Mourning can be lived as a necessary but dangerous stage of the re-cycle process of lthe living Gilgoule in Hebrew spring from Agole Round Gal Wave Galgal Wheel Gal Ad Tomb Gilgole Rebirth Golgoleth Human skull Despite the diversity of funeral rites the human skull Goulgolet condenses most of the experiences of death into reason to live This allow to better understand the reasons for the persistence survival mourning in a contemporary world imaginary